PEMAHAMAN TERHADAP PETANI KECIL SEBAGAI LANDASAN KEBIJAKAN PEMBANGUNAN PERTANIAN (Forum Penelitian Agro Ekonomi, 2013)
Improving the farmers’ welfare is one of goals in agricultural development policy. Inadequate government’s concern to farmers is observed from the definition of farmers in various regulations and understanding of small farmers’ existence, role and characters. Lacks of understanding and taking side to small farmers are indicated by absence of using the term of "small farmers" in various government policies. This paper reviews various thoughts, as well as development and implementation of agricultural policies with respect to farmers’ welfare improvement. The results show the weak understanding on, no partiality, and even unfair treatment to small farmers. Thus, in the future the concept of "small farmers" must be unequivocally expressed in order to make their potential more environmentally friendly and independently.